1986
DOI: 10.1067/mva.1986.avs0030140
|View full text |Cite
|
Sign up to set email alerts
|

The superiority of synthetic arterial grafts over autologous veins in carotid-subclavian bypass

Abstract: From May 1964 to June 1983, 36 carotid-subclavian bypasses were done in 36 patients who had symptomatic lesions at the origin of the common carotid and/or subclavian arteries at the Center for Health Sciences of the University of California, Los Angeles. Ages ranged from 28 to 82 years (mean, 58 years). Eighteen bypasses were done with prosthetic grafts, 13 done with autogenous vein, and five were transpositions with primary anastomosis of the subclavian and carotid arteries. Follow-up was available on all pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
5

Year Published

1991
1991
2007
2007

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 0 publications
0
28
0
5
Order By: Relevance
“…Extra-anatomical bypass, namely CSBG, and carotid-subclavian transposition, were proposed as alternatives, which offered similar patency rates with reduced morbidity and mortality. [14][15][16][17][18][19][20][21][22] Carotid-subclavian transposition was touted to eliminate the need for ¤ ¤ prosthetic material in the neck. Infection rates are invariably low in this operation, and the decision to perform CSBG versus carotidsubclavian transposition has been predominantly based on surgeon preference.…”
Section: Discussionmentioning
confidence: 99%
“…Extra-anatomical bypass, namely CSBG, and carotid-subclavian transposition, were proposed as alternatives, which offered similar patency rates with reduced morbidity and mortality. [14][15][16][17][18][19][20][21][22] Carotid-subclavian transposition was touted to eliminate the need for ¤ ¤ prosthetic material in the neck. Infection rates are invariably low in this operation, and the decision to perform CSBG versus carotidsubclavian transposition has been predominantly based on surgeon preference.…”
Section: Discussionmentioning
confidence: 99%
“…They found that 20% of autologous vein grafts underwent stenosis compared to 5% among the ePTFE grafts 85. In an earlier study involving carotid–subclavian bypasses, 94% of ePTFE grafts were patent at 5 years compared to 58% for autologous veins ( p < 0.01) 86. All these results suggest that ePTFE grafts are comparable if not better than autologous vein grafting.…”
Section: Prosthetic Bypass Graftsmentioning
confidence: 94%
“…On this basis, we consider that grafts with larger diameters may be preferable. Vein has been the preferred conduit in many studies; however, Rockman et al 7 and Ziomek et al 10 showed a higher graft failure rate when using vein compared with PTFE for CAB. Also, Lauder et al reported a comparatively poor 83% freedom from re‐stenosis rate at 2 years in a series of 50 vein graft CAB, with most graft failures occurring within the first 9 months 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Carotid artery bypass using autogenous or synthetic conduits has previously been reported with assisted primary patency rates of 87–100% being achieved at 5 years 2,4–6,10 . Five‐year freedom from stroke at 92% is also high and compares favourably with the results of CEA 5 …”
Section: Introductionmentioning
confidence: 97%